Comparison of Career Decision Difficulties: Reviewed Based On Gender and Its Affecting Aspects - Fatimah, Siti (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2020)
This article reviews the results of a descriptive analytical study of the career decision making profile of guidance and counseling students at IKIP Siliwangi by applying the career decision difficulty questionnaire from Itamar Gati et al. The subjects in this study were 170 students. The results of this study are to examine the studentsâ€™ difficulties in making career decisions related to: (1). lack of knowledge about the steps involved in the career decision making process; (2). lack of information about self (3). lack of information about the type of work; (4). lack of information about how to obtain additional information. The data obtained are tabulated and analyzed to get the results of the statistical description. The result of data analysis found that the level of students difficultues in making career decision categorized moderate.Â The statistical test on differences of difficulty of career decision making based on gender showed that male students are more difficult in making career decisions.